PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP VOLUME PENJUALAN PT. MARTINA BERTO PERIODE 2011 - 2020 - Krisma Amelia; Reza Reza; Noor Ellyawati (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determine the effect of Promotional Costs and Distribution Costs on Sales Volume of PT. Martina Berto for the period 2011 – 2020. The data used in this study is secondary data that can be accessed on the Indonesia Stock Exchange (IDX) website. Based on the results of the t-test on the variable cost of promotion obtained a significance value of 0.018, this value is smaller than the significance level of 0.05, which means that the variable Promotional Costs has a partial effect on the Sales Volume of PT. Martina Berto for the period 2011 - 2020, and the significance value obtained by the Distribution Cost variable is 0.222 where this value is greater than the significance level of 0.05, so the distribution cost variable does not partially affect the sales volume of PT. Martina Berto for the 2011-2020 period. Based on the results of the F test obtained the value of Sig. of 0.038 <0.05, it can be concluded that Promotional Costs and Distribution Costs have a simultaneous effect on the Sales Volume of PT. Martina Berto for the period 2011 - 2020. The conclusion of this study is that promotional costs have a partial effect on sales volume while distribution costs have no significant effect. partial to sales volume. Promotion costs and distribution costs simultaneously affect the sales volume of PT. Martina Berto. From this research, it is expected that the company can continue to increase the allocation of promotion costs and review the allocation of distribution costs incurred so that the company's goals in achieving high sales volume can be achieved. Keywords: Promotional Costs, Distribution Costs, Sales Volume